2007
DOI: 10.1271/bbb.60630
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedants againstLocusta migratoriafrom the Japanese Cedar,Cryptomeria japonica

Abstract: (1S,6R)-2,7(14),10-bisabolatrien-1-ol-4-one and (+)-7(14),10-bisaboladien-1-ol-4-one were isolated and identified from Cryptomeria japonica as antifeedants against Locusta migratoria L. which is well known as a serious pest to cereals throughout the world. These compounds strongly inhibited the feeding of L. migratoria only when they were combined, but each compound alone did not show any activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…76 Compounds 96 and 97, from Cryptomeria japonica, have been identified as antifeedants against Locusta migratoria when they are combined, but neither of these sesquiterpenes alone showed any activity. 77 Chromatography of an extract of the red alga Laurencia microcladia 78 afforded the bisabolane alcohol 98. Cimino and co-workers 79 have isolated two new unusual nitrogenous sesquiterpenes 99 and 100 from the Hainan sponge Axinyssa aff.…”
Section: Bicyclofarnesanementioning
confidence: 99%
“…76 Compounds 96 and 97, from Cryptomeria japonica, have been identified as antifeedants against Locusta migratoria when they are combined, but neither of these sesquiterpenes alone showed any activity. 77 Chromatography of an extract of the red alga Laurencia microcladia 78 afforded the bisabolane alcohol 98. Cimino and co-workers 79 have isolated two new unusual nitrogenous sesquiterpenes 99 and 100 from the Hainan sponge Axinyssa aff.…”
Section: Bicyclofarnesanementioning
confidence: 99%
“…The various spectral data for synthetic (AE)-2 are in good agreement with those for the natural product. 1) We observed that the diastereomeric ratio changed from 1:1 in 5 to 2:3 in (AE)-2/2 0 during the final two steps. As mentioned by Nakahata et al, 5) this change might have been due to epimerization at the C3 stereogenic center under basic TBAF treatment conditions.…”
mentioning
confidence: 66%
“…Reduction or complete inhibition of feeding using organic derivatives, crude plant extracts and/or pure allelochemicals as antifeedants has been demonstrated in several orders such as Lepidoptera,6–8 Coleoptera,9–11 Hemiptera,12, 13 and Orthoptera 14–17. Therefore, antifeedants constitute a useful element for integrated pest management strategies because they can protect plants from insect herbivory by making the host less palatable.…”
Section: Introductionmentioning
confidence: 99%